1998
DOI: 10.1161/01.cir.97.6.535
|View full text |Cite|
|
Sign up to set email alerts
|

Incremental Prognostic Value of Myocardial Perfusion Single Photon Emission Computed Tomography for the Prediction of Cardiac Death

Abstract: Myocardial perfusion SPECT yields incremental prognostic information toward the identification of cardiac death. Patients with mildly abnormal scans after exercise stress are at low risk for cardiac death but intermediate risk for nonfatal myocardial infarction and thus may benefit from a noninvasive strategy and may not require invasive management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
563
10
55

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,134 publications
(655 citation statements)
references
References 30 publications
(20 reference statements)
27
563
10
55
Order By: Relevance
“…It is therefore even more intriguing that in our patient population with EF drop the event rate appears to be significantly higher than in controls, with an incidence of 5% for hard events and of 17.5% for soft events. These values appear at least comparable and possibly superior to those previously reported for patients with mild to moderate perfusion abnormalities [8,17,18].…”
Section: Comparison With Previous Studiessupporting
confidence: 87%
“…It is therefore even more intriguing that in our patient population with EF drop the event rate appears to be significantly higher than in controls, with an incidence of 5% for hard events and of 17.5% for soft events. These values appear at least comparable and possibly superior to those previously reported for patients with mild to moderate perfusion abnormalities [8,17,18].…”
Section: Comparison With Previous Studiessupporting
confidence: 87%
“…13 Although the study setting might differ among studies, the event rate was generally lower in Japan compared with those of Western studies. 6,9,10,13,14 The annual hard event rate in normal myocardial perfusion SPECT was found to be low (0.63%) in the subanalysis. 15 The importance of diabetes mellitus has been emphasized in a Japanese population, which has been also demonstrated in Western studies.…”
Section: Event Rate In the J-access Studymentioning
confidence: 74%
“…Hachamovitch et al showed that over a mean follow up of 642 days in 5183 patients, 277 hard events (5.3%) occurred, including 3.0% cardiac death rate, 2.3% myocardial infarction rate. 9 Petix et al showed that during follow-up (median 13 months) of 333 patients, 17 cardiac deaths (5.1%) and 13 nonfatal acute myocardial infarctions (3.9%) occurred. 13 Although the study setting might differ among studies, the event rate was generally lower in Japan compared with those of Western studies.…”
Section: Event Rate In the J-access Studymentioning
confidence: 99%
“…The cardiac event-free survival at 3 years was 83.8% and 79.9%, respectively, in patients with SSS ≥5 and those with SDS ≥1 (Figs 1,2), whereas the 3-year survival rate was 98.6% in patients with SSS <4, which is recognized as within normal range. 9,17 Thus, based on scintigraphic findings, the risk for future cardiac events can be noninvasively predicted, even in Japanese elderly patients aged 75 years or more with known or suspected CAD. The fact that the mean SDS was 6.4 in 18 patients who subsequently had a cardiac event, and that SDS ≥1 was the only independent predictor for major cardiac events by multivariate analysis in this group of patients, suggests that elderly patients with scintigraphic evidence of myocardial ischemia should be followed carefully if treated medically.…”
Section: Discussionmentioning
confidence: 99%